Polysiloxane multifunctional anticorrosive coating and preparation method thereof
By introducing composite modified boron nitride and secondary modified glass flakes into polysiloxane coatings, it is used in concert to improve waterproof, bacteriostatic, anti-corrosion and wear resistance, the problem of insufficient waterproof and corrosion resistance of existing coatings is solved, and better overall performance and longer service life are achieved.
Patent Information
- Application Number
- CN202510112906.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing polysiloxane coatings have shortcomings in waterproofing and corrosion resistance, resulting in accelerated water molecular penetration and aging of matrix materials, increasing maintenance costs.
The composite modified boron nitride and secondary modified glass flakes were prepared by using raw materials such as vinyl-terminated methylphenyl polysiloxane, epoxy resin and anhydrous ethanol through stirring and ball milling, and used in the multi-functional anticorrosion coating of polysiloxane.
It significantly improves the waterproof, antibacterial, anticorrosion and wear resistance of the coating, meets environmental protection standards, is simple to operate, is low in cost, and is suitable for industrial production.
Smart Images

Figure BDA0005257091650000151 
Figure BDA0005257091650000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a polysiloxane multifunctional anticorrosive coating and a preparation method thereof. Background Art
[0002] Industrial anti-corrosion coatings are mainly used on various metal surfaces to protect and beautify them, such as corrosion resistance, rust resistance, atmospheric aging resistance, and wear resistance. Polysiloxane coatings have strong anti-aging and anti-corrosion properties, and show excellent weather resistance and gloss and color retention. They will not lose gloss or fade after long-term use. Therefore, they are often used for surface corrosion protection of building steel structures, highway guardrails, transformers, railway bridges, transportation facilities, mechanical equipment, etc. With the advancement of science and technology and social development, in order to meet the demand for repeated coating performance in the industrial field, it is necessary to provide polysiloxane coatings with better overall performance and multifunctionality.
[0003] CN112708077A discloses a waterborne polysiloxane resin, a topcoat and a preparation method thereof. The waterborne polysiloxane resin provided by the invention increases the silicon content of the resin by using divinyl-terminated polysiloxane. At the same time, the synergistic coordination of divinyl-terminated polysiloxane and other components effectively improves the weather resistance and flexibility of the waterborne polysiloxane resin. The waterborne polysiloxane topcoat prepared using the waterborne polysiloxane resin has excellent inertness, hardness, adhesion, chemical resistance, high temperature resistance, weather resistance, UV resistance and wear resistance, but the waterborne polysiloxane topcoat has poor waterproof performance, which will cause water molecules to penetrate and shorten the life of the structure.
[0004] CN117801670A discloses an isocyanate-cured polysiloxane coating and a preparation method thereof. The isocyanate-cured polysiloxane coating provided by the invention comprises the following components: component A and component B; the component A comprises the following raw materials in parts by weight: 10-30 parts of hydroxy acrylic resin, 0.5-3 parts of anti-settling agent, 0.5-1 parts of dispersant, 0.1-1 parts of defoaming agent, 10-30 parts of titanium dioxide, 10-30 parts of barium sulfate, 30-50 parts of polysiloxane resin, 0.1-1 parts of light stabilizer, and 3-6 parts of solvent; the component B comprises the following raw materials in parts by weight: 100 parts of curing agent; the coating provided by the invention has high solid content, can form a film of 80-120um in one time, has excellent light and color retention performance, and has the advantages of environmental protection and convenient construction, but the coating has unsatisfactory anti-corrosion performance, which will lead to accelerated aging of the covered substrate material and increase maintenance costs. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, the present invention provides a polysiloxane multifunctional anti-corrosion coating and a preparation process thereof. The polysiloxane multifunctional anti-corrosion coating provided by the present invention has excellent waterproof, antibacterial, anti-corrosion and wear-resistant properties, meets environmental protection standards, is simple to operate, has low cost, and is suitable for industrial production.
[0006] To achieve the above object, the present invention provides a preparation process of a polysiloxane multifunctional anti-corrosion coating, comprising the following steps:
[0007] Vinyl-terminated methylphenyl polysiloxane, epoxy resin and anhydrous ethanol are put into a stirring tank and mixed and stirred at 500-800rpm and 30-50°C for 20-30min to obtain a mixed slurry A; then the mixed slurry A, composite modified boron nitride, sodium montmorillonite, leveling agent, dispersant and film-forming aid are added to a ball mill and ground to a fineness of ≤30μm to obtain a mixed slurry B; then a curing agent and a defoaming agent are added to the mixed slurry B, mixed and stirred at 80-120MPa and 1000-1500rpm for 30-60min to obtain a polysiloxane multifunctional anti-corrosion coating; the polysiloxane multifunctional anti-corrosion coating is applied and dried to obtain a polysiloxane multifunctional anti-corrosion coating;
[0008] Alternatively, vinyl-terminated methylphenyl polysiloxane, epoxy resin and anhydrous ethanol are put into a stirring tank and mixed and stirred at 500-800rpm and 30-50°C for 20-30min to obtain a mixed slurry A; then the mixed slurry A, composite modified boron nitride, sodium montmorillonite, filler, leveling agent, dispersant and film-forming aid are added to a ball mill and ground to a fineness of ≤30μm to obtain a mixed slurry B; then a curing agent and a defoaming agent are added to the mixed slurry B, mixed and stirred at 80-120MPa and 1000-1500rpm for 30-60min to obtain a polysiloxane multifunctional anti-corrosion coating; the polysiloxane multifunctional anti-corrosion coating is applied and dried to obtain a polysiloxane multifunctional anti-corrosion coating.
[0009] Preferably, the weight ratio of each raw material component is:
[0010] 40-60 parts of vinyl-terminated methylphenyl polysiloxane, 5-15 parts of epoxy resin, 1-3 parts of composite modified boron nitride, 10-15 parts of sodium montmorillonite, 1-3 parts of leveling agent, 1-3 parts of curing agent, 1-2 parts of dispersant, 1-2 parts of film-forming aid, 1-2 parts of defoaming agent, 5-12 parts of anhydrous ethanol;
[0011] Or, 40-60 parts of vinyl-terminated methylphenyl polysiloxane, 5-15 parts of epoxy resin, 1-3 parts of composite modified boron nitride, 10-15 parts of sodium montmorillonite, 4-8 parts of filler, 1-3 parts of leveling agent, 1-3 parts of curing agent, 1-2 parts of dispersant, 1-2 parts of film-forming aid, 1-2 parts of defoaming agent, and 5-12 parts of anhydrous ethanol.
[0012] Preferably, the epoxy resin is selected from one of epoxy resin E20, epoxy resin E44 and epoxy resin E51.
[0013] Preferably, the preparation method of the composite modified boron nitride comprises the following steps, measured by weight:
[0014] S1. Add 0.5-2 parts of hexagonal boron nitride and 0.5-2 parts of aniline to 40-60 parts of phosphoric acid with a concentration of 0.5-2 mol / L, mix and stir evenly, and then ultrasonically treat for 25-40 minutes to obtain a mixed solution A; add 3-4 parts of sodium persulfate to 40-60 parts of phosphoric acid with a concentration of 0.5-2 mol / L, mix and stir evenly, to obtain a mixed solution B; add the mixed solution B to the mixed solution A, and then continuously mix and stir in an ice water bath for 2-4 hours, then filter, wash with ethanol 2-3 times, then wash with water 2-3 times, and then dry to obtain surface-modified boron nitride;
[0015] S2. The surface modified boron nitride, modifier and water are mixed and stirred evenly in a weight ratio of 1:0.05-0.2:4-6, and then ultrasonically treated for 20-40 minutes, and then vacuum dried at 45-55° C. for 4-6 hours to obtain composite modified boron nitride.
[0016] Preferably, in step S2, the modifier is selected from one of sodium molybdate, sodium titanate and sodium tungstate.
[0017] The present invention mixes boron nitride with aniline monomer under acidic conditions, adds an initiator to start the polymerization reaction, and the aniline monomer forms polyaniline on the surface of the boron nitride through oxidative polymerization to obtain surface-modified boron nitride, thereby enhancing the interaction between polyaniline and boron nitride and improving the dispersibility and adhesion of polyaniline on the surface of the boron nitride. After that, the surface-modified boron nitride is mixed with a modifier, and the anti-corrosion ions such as molybdate ions, tungstate ions, and titanate ions generated by the modifier are fixed on the surface-modified boron nitride by ultrasonic treatment, which may form coordination bonds with functional groups on the surface of the surface-modified boron nitride or by van der Waals force physical adsorption, thereby enhancing the load and stability of the anti-corrosion ions on the surface of the boron nitride, so that the anti-corrosion ions are uniformly dispersed and loaded on the surface-modified boron nitride to obtain a composite modified boron nitride. The load of the anti-corrosion ions on the composite modified boron nitride can be slowly released to exert its corrosion inhibition effect.
[0018] The present invention introduces composite modified boron nitride in the coating preparation process, which is beneficial to improving the waterproofness, corrosion resistance and wear resistance of the coating. Hexagonal boron nitride has a layered structure, which can form a physical barrier and a low friction interface in the coating, prevent water molecules and corrosive media from penetrating into the metal surface and reduce the wear of the coating during the friction process, but the surface energy of hexagonal boron nitride is relatively low, and the interaction force between layers is strong, which may cause it to be difficult to disperse in the resin matrix. In view of this, the introduction of polyaniline in the composite modified boron nitride preparation process of the present invention can enhance the binding force between hexagonal boron nitride and the resin matrix, which is beneficial to improving the dispersibility of hexagonal boron nitride in the resin matrix, improving its compatibility with other raw materials, and improving the overall performance of the coating. In addition, the polyaniline on the surface of the composite modified boron nitride, as a conductive polymer with good chemical stability, can participate in the electrochemical reaction of the metal surface, and by accepting the electrons released during the metal dissolution process, a passivation film is formed to inhibit the metal anodic oxidation process, thereby improving the anti-corrosion performance of the coating. In addition, the anti-corrosion ions loaded on the composite modified boron nitride may be continuously released during the use of the coating, reacting with the metal surface to form a dense oxide film, preventing the corrosive medium from reaching the metal surface and providing a long-term corrosion inhibition effect.
[0019] Preferably, in parts by weight, step S1 in the method for preparing the composite modified boron nitride may also be:
[0020] Disperse 1-3 parts of hexagonal boron nitride in 80-100 parts of Tris buffer with a pH value of 8.0-8.5, and then ultrasonically treat for 0.5-2 hours to obtain a dispersion; add 0.5-2 parts of dopamine hydrochloride to the above dispersion, place it in a 55-65°C water bath and mix and stir for 22-25 hours, then filter, wash with ethanol 2-3 times, then wash with water 2-3 times, and then dry to obtain surface modified boron nitride.
[0021] The present invention finds that by mixing hexagonal boron nitride and dopamine hydrochloride under alkaline conditions, a polydopamine coating can be formed on the surface of the boron nitride by polymerizing dopamine to obtain surface-modified boron nitride, thereby increasing the interaction between the boron nitride and the boron nitride, and improving the dispersibility and adhesion of polyaniline on the surface of the boron nitride. The functional groups on the surface of the polydopamine may undergo ion exchange or chelation with the anticorrosive ions generated by the modifier, thereby increasing the load of the anticorrosive ions on the surface of the boron nitride and improving its anticorrosive performance.
[0022] Preferably, the leveling agent is selected from one of German BYK-323, BYK-345 and BYK-326.
[0023] Preferably, the curing agent is selected from at least one of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, anilinomethyltrimethoxysilane and anilinomethyltriethoxysilane.
[0024] Preferably, the dispersant is selected from at least one of German BYK-153, BYK-154, and BYK-156.
[0025] Preferably, the film-forming aid is selected from at least one of ethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, propylene glycol methyl ether and propylene glycol butyl ether.
[0026] Preferably, the defoaming agent is a silicone polyether defoaming agent.
[0027] Preferably, the filler is secondary modified glass flakes, and the preparation method thereof comprises the following steps, calculated by weight:
[0028] 4-6 parts of water, 4-6 parts of silane coupling agent KH-560, 25-35 parts of anhydrous ethanol and 8-12 parts of glass flakes are placed at room temperature and 300-600rpm and mixed for 22-25 hours to obtain a mixed solution A; the mixed solution A is centrifuged, the precipitate is collected, washed with water and vacuum dried at 55-65°C to obtain a primary modified glass flake; 1-3 parts of acetic acid and 1-3 parts of water are added to 60-68 parts of anhydrous ethanol, and the pH is adjusted to 3-4 with dilute hydrochloric acid to obtain solution A; 8-12 parts of tetrabutyl titanate are added to 60-68 parts of anhydrous ethanol and mixed and stirred. , obtaining solution B; then adding solution B to solution A at 600-800rpm and 24-26°C and continuously mixing and stirring for 22-25h to obtain titanium dioxide colloid; mixing 1.5-3 parts of primary modified glass flakes, 25-35 parts of anhydrous ethanol, 0.01-0.1 parts of phytic acid and 0.01-0.1 parts of titanium dioxide colloid, placing at 300-500rpm and 75-85°C and mixing and stirring for 3-5h to obtain a mixed solution B; centrifuging the mixed solution B, collecting the precipitate, washing with water and drying in vacuo at 55-65°C to obtain a secondary modified glass flake.
[0029] Glass flakes have a layered structure similar to fish scales, and have excellent corrosion resistance, high mechanical strength and wear resistance. The unique layered structure of glass flakes enables glass flakes to form an effective barrier in the coating, reducing the penetration of corrosive media. Therefore, they are often used as fillers in anti-corrosion coatings to improve the anti-penetration performance of the coating. However, the interfacial bonding strength and dispersibility between glass flakes and the matrix resin are not ideal.
[0030] In order to solve the problems existing in glass flakes, the present invention uses a silane coupling agent KH-560 to modify the surface of glass flakes. The organic functional groups in the molecular structure of the silane coupling agent KH-560 can chemically react with the hydroxyl groups on the surface of the glass flakes to form chemical bonds, thereby modifying the surface of the glass flakes, improving their surface activity and introducing epoxy groups to obtain primary modified glass flakes; the primary modified glass flakes are mixed with phytic acid and titanium dioxide colloid, and the phosphorus hydroxyl groups in the phytic acid can undergo a ring-opening reaction with the epoxy groups on the surface of the surface modified glass flakes to form stable COP bonds, thereby grafting the phytic acid onto the surface of the glass flakes; at the same time, the titanium atoms in the titanium dioxide colloid prepared by the present invention can undergo a coordination reaction with the oxygen atoms in the phosphate groups in the phytic acid to form Ti-OP bonds, which can be grafted onto the surface of the glass flakes by forming coordination bonds to form secondary modified glass flakes.
[0031] The present invention finds that introducing the secondary modified glass flakes prepared by the present invention as fillers during the coating preparation process is beneficial to increasing the waterproofness, corrosion resistance, antibacterial and wear resistance of the coating. The surface modified glass flakes with silane coupling agent KH-560 improve the surface activity of the glass flakes and give them epoxy groups to enhance the dispersibility and compatibility of the glass flakes with epoxy resins, which helps to improve the overall performance of the coating. Phytic acid is introduced into the secondary modified glass flake structure. Phytic acid has a strong metal ion chelating ability and can combine with metal ions required for bacterial growth to form a stable chelate, thereby depriving bacteria of these metal ions required, inhibiting their growth and reproduction, and having certain antibacterial properties; at the same time, during the modification of the glass flakes, the titanium dioxide colloid reacts with the oxygen atoms in the phytic acid through its titanium atoms to form Ti-OP bonds, thereby anchoring the photocatalytic antibacterial agent titanium dioxide on the surface of the glass flakes. The active oxygen species produced by titanium dioxide under light conditions can destroy the cell walls and cell membranes of bacteria, thereby causing leakage of cell contents and bacterial death, and improving the antibacterial performance of the coating. Therefore, the secondary modified glass flakes prepared by combining the photocatalytic antibacterial agent titanium dioxide with phytic acid on the grafted glass flakes can not only expand the spectral response range of the photocatalytic antibacterial effect of titanium dioxide, but also can simultaneously exert the synergistic effect of titanium dioxide and phytic acid in the antibacterial effect, that is, have a dual-effect bactericidal effect. In addition, the present invention finds that compared with ordinary titanium dioxide materials, the titanium dioxide colloid prepared by the present invention has a higher specific surface area, which may prompt it to form a stronger surface charge. The surface charge helps to maintain the stability of the colloid and prevent particle aggregation, thereby maintaining the high reactivity of the colloid particles and effective contact with the phytic acid molecules, and the enhanced surface charge helps to reduce the activation energy of the coordination reaction, making it easier for the oxygen atoms in the phytic acid molecules to approach the titanium atoms on the surface of the titanium dioxide colloid particles, forming a stable Ti-OP coordination bond, thereby increasing the durability of the titanium dioxide colloid in the coating. Moreover, during the modification process, titanium dioxide colloid can form a stable encapsulating adsorption layer on the surface of glass flakes through chemical bonding and physical adsorption, thereby increasing the surface roughness of the glass flakes, enabling them to better combine with the matrix resin, improving the coating adhesion, wear resistance and anti-permeability, and thus improving the anti-corrosion and waterproof properties.
[0032] The present invention also provides a polysiloxane multifunctional anti-corrosion coating, which is prepared by the above process.
[0033] Beneficial effects of the present invention:
[0034] 1. Compared with the prior art, the present invention prepares a polysiloxane multifunctional anticorrosion coating by reasonable proportion, utilizing the interaction between various substances, and optimizing the preparation process parameters. After the coating is dried, a polysiloxane multifunctional anticorrosion coating is obtained. The anticorrosion coating provided by the present invention not only has good wear resistance and waterproof performance, but also improves the corrosion protection of the coating on the metal substrate, improves the overall anticorrosion performance, and achieves the effect of extending the life of the metal.
[0035] 2. Compared with the prior art, the present invention improves the dispersibility of hexagonal boron nitride in the matrix resin by surface modification of hexagonal boron nitride and introducing polyaniline, and then prepares composite modified boron nitride by mixing with a modifier to load anticorrosive ions, giving boron nitride excellent anticorrosive properties; and in the coating preparation process, the glass flakes are modified once by using silane coupling agent KH-560 to increase the dispersibility of the glass flakes, and then phytic acid and titanium dioxide colloid are introduced to modify the glass flakes for a second time to obtain secondary modified glass flakes, thereby improving their antibacterial properties. The composite modified boron nitride and secondary modified glass flakes prepared by the present invention are not only well dispersed in the polysiloxane multifunctional anticorrosive coating, but also have good compatibility with the system, and the synergistic use of the secondary modified glass flakes and the composite modified boron nitride can improve the antibacterial, anticorrosive, waterproof and wear resistance of the polysiloxane multifunctional anticorrosive coating, which is beneficial to improving the durability of the coating and increasing the service life of the coating. DETAILED DESCRIPTION
[0036] Parameters for specific chemical substances used, sources.
[0037] Hexagonal boron nitride, specification: 3μm;
[0038] Titanium dioxide, specification: 100nm;
[0039] Glass flakes, specification: 5μm;
[0040] N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, CAS No.: 5089-72-5;
[0041] Sodium montmorillonite, content: 90%, particle size: 600 mesh, whiteness: 80;
[0042] Epoxy resin E44, brand: 6101 (E44), brand: Phoenix;
[0043] Vinyl-terminated methylphenyl polysiloxane, grade: P909930, brand: McLean;
[0044] Silicone polyether defoamer, brand: ZY-6310, comes from Shanghai Ziyi Chemical Co., Ltd.
[0045] Example 1
[0046] A preparation process of a polysiloxane multifunctional anti-corrosion coating comprises the following steps:
[0047] 50 parts by weight of vinyl-terminated methylphenyl polysiloxane, 10 parts by weight of epoxy resin E44 and 10 parts by weight of anhydrous ethanol were put into a stirring tank and mixed and stirred at 650 rpm and 40°C for 28 minutes to obtain a mixed slurry A; then the mixed slurry A, 2 parts by weight of composite modified boron nitride, 12 parts by weight of sodium montmorillonite, 6 parts by weight of secondary modified glass flakes, 2 parts by weight of BYK-323, 1.2 parts by weight of BYK-153 and 1.5 parts by weight of Add 2 parts by weight of dipropylene glycol butyl ether into a ball mill and grind to a fineness of ≤30 μm to obtain a mixed slurry B; then add 2 parts by weight of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 1.5 parts by weight of a silicone polyether defoaming agent to the mixed slurry B, mix and stir for 40 minutes under the conditions of 100 MPa and 1200 rpm to obtain a polysiloxane multifunctional anti-corrosion coating; apply the polysiloxane multifunctional anti-corrosion coating, and dry to obtain a polysiloxane multifunctional anti-corrosion coating.
[0048] The preparation method of the composite modified boron nitride comprises the following steps:
[0049] S1. Add 1 part by weight of hexagonal boron nitride and 1 part by weight of aniline to 50 parts by weight of 1 mol / L phosphoric acid, mix and stir evenly, and then ultrasonicate for 30 minutes to obtain a mixed solution A; add 3.3 parts by weight of sodium persulfate to 50 parts by weight of 1 mol / L phosphoric acid, mix and stir evenly to obtain a mixed solution B; add the mixed solution B to the mixed solution A, and then continuously mix and stir in an ice-water bath for 3 hours, then filter, wash with ethanol 3 times, then wash with water 3 times, and then dry to obtain surface-modified boron nitride;
[0050] S2. The surface modified boron nitride, sodium molybdate and water are mixed and stirred evenly in a weight ratio of 1:0.1:5, and then ultrasonically treated for 30 minutes, and then vacuum dried at 50° C. for 5 hours to obtain a composite modified boron nitride.
[0051] The preparation method of the secondary modified glass flakes comprises the following steps:
[0052] 5 parts by weight of water, 5 parts by weight of silane coupling agent KH-560, 30 parts by weight of anhydrous ethanol and 10 parts by weight of glass flakes were placed at room temperature and stirred at 400 rpm for 24 hours to obtain a mixed solution A; the mixed solution A was centrifuged, the precipitate was collected, washed with water and then dried in vacuo at 60°C to obtain a primary modified glass flake; 2.5 parts by weight of acetic acid and 2.5 parts by weight of water were added to 66 parts by weight of anhydrous ethanol, and the pH was adjusted to 3 with dilute hydrochloric acid (0.1 mol / L) to obtain a solution A; 10 parts by weight of tetrabutyl titanate was added to The mixture was mixed and stirred in 66 parts by weight of anhydrous ethanol to obtain solution B; solution B was then added to solution A at 750 rpm and 25°C and the mixing and stirring was continued for 24 hours to obtain titanium dioxide colloid; 2 parts by weight of primary modified glass flakes, 30 parts by weight of anhydrous ethanol, 0.06 parts by weight of phytic acid and 0.04 parts by weight of titanium dioxide colloid were mixed and stirred at 400 rpm and 80°C for 4 hours to obtain a mixed solution B; the mixed solution B was centrifuged, the precipitate was collected, washed with water and dried in a vacuum at 60°C to obtain secondary modified glass flakes.
[0053] Example 2
[0054] A preparation process of a polysiloxane multifunctional anti-corrosion coating, which is different from Example 1 in that the preparation method of the composite modified boron nitride comprises the following steps:
[0055] S1. Add 1 part by weight of hexagonal boron nitride and 1 part by weight of aniline to 50 parts by weight of 1 mol / L phosphoric acid, mix and stir evenly, and then ultrasonicate for 30 minutes to obtain a mixed solution A; add 3.3 parts by weight of sodium persulfate to 50 parts by weight of 1 mol / L phosphoric acid, mix and stir evenly to obtain a mixed solution B; add the mixed solution B to the mixed solution A, and then continuously mix and stir in an ice-water bath for 3 hours, then filter, wash with ethanol 3 times, then wash with water 3 times, and then dry to obtain surface-modified boron nitride;
[0056] S2. The surface modified boron nitride, sodium tungstate and water are mixed and stirred evenly in a weight ratio of 1:0.1:5, and then ultrasonically treated for 30 minutes, and then vacuum dried at 50° C. for 5 hours to obtain a composite modified boron nitride.
[0057] Example 3
[0058] A preparation process of a polysiloxane multifunctional anti-corrosion coating, which is different from Example 1 in that the preparation method of the composite modified boron nitride comprises the following steps:
[0059] S1. Add 1 part by weight of hexagonal boron nitride and 1 part by weight of aniline to 50 parts by weight of 1 mol / L phosphoric acid, mix and stir evenly, and then ultrasonicate for 30 minutes to obtain a mixed solution A; add 3.3 parts by weight of sodium persulfate to 50 parts by weight of 1 mol / L phosphoric acid, mix and stir evenly to obtain a mixed solution B; add the mixed solution B to the mixed solution A, and then continuously mix and stir in an ice-water bath for 3 hours, then filter, wash with ethanol 3 times, then wash with water 3 times, and then dry to obtain surface-modified boron nitride;
[0060] S2. The surface modified boron nitride, sodium titanate and water are mixed and stirred evenly in a weight ratio of 1:0.1:5, and then ultrasonically treated for 30 minutes, and then vacuum dried at 50° C. for 5 hours to obtain composite modified boron nitride.
[0061] Example 4
[0062] A preparation process of a polysiloxane multifunctional anti-corrosion coating, which is different from Example 1 in that the preparation method of the composite modified boron nitride comprises the following steps:
[0063] S1. Dispersing 2 parts by weight of hexagonal boron nitride in 95 parts by weight of Tris buffer with a pH value of 8.2, and then ultrasonically treating for 1 hour to obtain a dispersion; adding 1 part by weight of dopamine hydrochloride to the above dispersion, placing in a 60° C. water bath and mixing and stirring for 24 hours, then filtering, washing with ethanol 3 times, then washing with water 3 times, and then drying to obtain surface-modified boron nitride;
[0064] S2. The surface modified boron nitride, sodium molybdate and water are mixed and stirred evenly in a weight ratio of 1:0.1:5, and then ultrasonically treated for 30 minutes, and then vacuum dried at 50° C. for 5 hours to obtain a composite modified boron nitride.
[0065] Example 5
[0066] A preparation process of a polysiloxane multifunctional anti-corrosion coating comprises the following steps:
[0067] 50 parts by weight of vinyl-terminated methylphenyl polysiloxane, 10 parts by weight of epoxy resin E44 and 10 parts by weight of anhydrous ethanol are put into a stirring tank and mixed and stirred at 650 rpm and 40° C. for 28 minutes to obtain a mixed slurry A; then the mixed slurry A, 2 parts by weight of composite modified boron nitride, 12 parts by weight of sodium montmorillonite, 2 parts by weight of BYK-323, 1.2 parts by weight of BYK-153 and 1.5 parts by weight of dipropylene glycol butyl ether are added to a ball mill and ground to a fineness of ≤30 μm to obtain a mixed slurry B; then 2 parts by weight of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 1.5 parts by weight of a silicone polyether defoamer are added to the mixed slurry B, mixed and stirred at 100 MPa and 1200 rpm for 40 minutes to obtain a polysiloxane multifunctional anti-corrosion coating; the polysiloxane multifunctional anti-corrosion coating is applied and dried to obtain a polysiloxane multifunctional anti-corrosion coating.
[0068] The preparation method of the composite modified boron nitride is consistent with that of Example 1.
[0069] Comparative Example 1
[0070] A preparation process of a polysiloxane multifunctional anti-corrosion coating, which is different from Example 1 in that the preparation method of the secondary modified glass flakes comprises the following steps:
[0071] 5 parts by weight of water, 5 parts by weight of silane coupling agent KH-560, 30 parts by weight of anhydrous ethanol and 10 parts by weight of glass flakes are placed at room temperature and 400 rpm and mixed and stirred for 24 hours to obtain a mixed solution A; the mixed solution A is centrifuged, the precipitate is collected, washed with water and then dried in a vacuum at 60°C to obtain a first-modified glass flake; 2 parts by weight of the first-modified glass flake, 30 parts by weight of anhydrous ethanol and 0.06 parts by weight of phytic acid are mixed, placed at 400 rpm and 80°C and mixed and stirred for 4 hours to obtain a mixed solution B; the mixed solution B is centrifuged, the precipitate is collected, washed with water and then dried in a vacuum at 60°C to obtain a second-modified glass flake.
[0072] Comparative Example 2
[0073] A preparation process of a polysiloxane multifunctional anti-corrosion coating comprises the following steps:
[0074] 50 parts by weight of vinyl-terminated methylphenyl polysiloxane, 10 parts by weight of epoxy resin E44 and 10 parts by weight of anhydrous ethanol were put into a stirring tank and mixed and stirred at 650 rpm and 40°C for 28 minutes to obtain a mixed slurry A; then the mixed slurry A, 2 parts by weight of composite modified boron nitride, 12 parts by weight of sodium montmorillonite, 6 parts by weight of glass flakes, 2 parts by weight of BYK-323, 1.2 parts by weight of BYK-153 and 1.5 parts by weight of Add dipropylene glycol butyl ether into a ball mill and grind to a fineness of ≤30 μm to obtain a mixed slurry B; then add 2 parts by weight of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 1.5 parts by weight of a silicone polyether defoamer to the mixed slurry B, mix and stir for 40 minutes at 100 MPa and 1200 rpm to obtain a polysiloxane multifunctional anti-corrosion coating; apply the polysiloxane multifunctional anti-corrosion coating, and dry to obtain a polysiloxane multifunctional anti-corrosion coating.
[0075] The preparation method of the composite modified boron nitride is consistent with that of Example 1.
[0076] Comparative Example 3
[0077] A preparation process of a polysiloxane multifunctional anti-corrosion coating comprises the following steps:
[0078] 50 parts by weight of vinyl-terminated methylphenyl polysiloxane, 10 parts by weight of epoxy resin E44 and 10 parts by weight of anhydrous ethanol are put into a stirring tank and mixed and stirred at 650 rpm and 40° C. for 28 minutes to obtain a mixed slurry A; then the mixed slurry A, 12 parts by weight of sodium montmorillonite, 6 parts by weight of secondary modified glass flakes, 2 parts by weight of BYK-323, 1.2 parts by weight of BYK-153 and 1.5 parts by weight of dipropylene glycol butyl ether are added to a ball mill and ground to a fineness of ≤30 μm to obtain a mixed slurry B; then 2 parts by weight of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 1.5 parts by weight of a silicone polyether defoamer are added to the mixed slurry B, mixed and stirred at 100 MPa and 1200 rpm for 40 minutes to obtain a polysiloxane multifunctional anti-corrosion coating; the polysiloxane multifunctional anti-corrosion coating is applied and dried to obtain a polysiloxane multifunctional anti-corrosion coating.
[0079] The preparation method of the secondary modified glass flakes is consistent with that in Example 1.
[0080] Comparative Example 4
[0081] A preparation process of a polysiloxane multifunctional anti-corrosion coating, which is different from Example 1 in that the preparation method of the secondary modified glass flakes comprises the following steps:
[0082] 5 parts by weight of water, 5 parts by weight of silane coupling agent KH-560, 30 parts by weight of anhydrous ethanol and 10 parts by weight of glass flakes are placed at room temperature and 400 rpm and mixed and stirred for 24 hours to obtain a mixed solution A; the mixed solution A is centrifuged, the precipitate is collected, washed with water and then dried in a vacuum at 60°C to obtain a first-modified glass flake; 2 parts by weight of the first-modified glass flake, 30 parts by weight of anhydrous ethanol, 0.06 parts by weight of phytic acid and 0.04 parts by weight of titanium dioxide are mixed, placed at 400 rpm and 80°C and mixed and stirred for 4 hours to obtain a mixed solution B; the mixed solution B is centrifuged, the precipitate is collected, washed with water and then dried in a vacuum at 60°C to obtain a second-modified glass flake.
[0083] Test Example 1
[0084] Antibacterial performance test
[0085] The antibacterial property test of the polysiloxane multifunctional anticorrosion coatings prepared in Examples 1-5 and Comparative Examples 1-4 was performed with reference to the standard "GB / T 21866-2008 Determination of Antibacterial Property and Antibacterial Effect of Antibacterial Coatings (Paint Films)"; the test bacteria were Escherichia coli (commercially available, AS1.90) and Staphylococcus aureus (commercially available, AS1.89); Escherichia coli and Staphylococcus aureus suspensions were prepared according to the standard method of "GB / T 21866-2008 Determination of Antibacterial Property and Antibacterial Effect of Antibacterial Coatings (Paint Films)" and set aside; polysiloxane multifunctional anticorrosion coating test plates of Examples 1-5 and Comparative Examples 1-4 with metal plates as substrates were prepared according to the standard method of "GB / T 21866-2008 Determination of Antibacterial Property and Antibacterial Effect of Antibacterial Coatings (Paint Films)" and set aside;
[0086] Test experiment: Take 0.5mL of the test inoculated bacterial solution and drip it onto the polysiloxane multifunctional anticorrosive coating sample and blank control sample prepared in Examples 1-5 and Comparative Examples 1-4, respectively, and use sterilized tweezers to pick up the sterilized covering film and cover the sample respectively. It must be flat and free of bubbles, so that the bacteria can evenly contact the sample, and place it in a sterilized plate to simulate the environment in which the polysiloxane multifunctional anticorrosive coating coating is located during actual application. Culture it for 24 hours under natural light, 37°C, and relative humidity RH of 95%; take out the sample cultured for 24 hours, add 20mL of washing solution, wash the sample and cover the film repeatedly, shake it thoroughly, take the washing solution and inoculate it into the nutrient agar medium (NA), and count the viable bacteria after culturing at 37°C for 24 hours. Determine the number of viable bacteria in the washing solution according to the method of GB / T4789.2. Calculate the antibacterial rate of each embodiment and comparative example according to the number of viable bacteria, and the antibacterial rate calculation formula is as follows:
[0087] R(%)=(BC) / B×100%
[0088] Where, R is the antibacterial rate; B is the average number of bacteria recovered from the blank control sample after 24 hours (cfu / piece); C is the average number of bacteria recovered from the polysiloxane multifunctional anticorrosive coating sample after 24 hours (cfu / piece);
[0089] Each group of samples was tested in parallel for 3 groups, and the average value was taken. The test results are shown in Table 1;
[0090] Anti-corrosion performance test
[0091] With reference to the standard "JG / T224-2007 Anticorrosive Coatings for Steel Structures in Construction", a steel plate with a size of 150 mm × 70 mm × 1.2 mm was selected as a test plate, and the polysiloxane multifunctional anticorrosive coatings prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 were respectively applied on the surface of the test plate, and a paint film with a thickness of 200 μm was obtained after conditioning for 24 hours at 25°C and a relative humidity of 50%, thereby obtaining a test sample; with reference to the national standard "GB / T1771-2007 Determination of Neutral Salt Spray Resistance of Paints and Varnishes", a salt spray resistance test was performed on each test sample, and the time when each test sample began to bubble or fall off was observed. Five groups were tested in each group, and the average value was taken. The test results are shown in Table 1.
[0092] Wear resistance test
[0093] The test samples of Examples 1-5 and Comparative Examples 1-4 were prepared with reference to the above anti-corrosion performance test method. With reference to the national standard "GB / T 1768-2006 Determination of Wear Resistance of Paints and Varnishes - Rotating Rubber Grinding Wheel Method", wear resistance tests were performed on each test sample at a temperature of 25°C and a relative humidity of 50%. The rotation speed of the abrasion tester was 60 r / min, the test time was 3 min, and the grinding wheel model CS-10F of Taber Industries, USA was used. The wear mass loss of each test sample was recorded. The wear mass loss calculation formula is as follows:
[0094] Wear mass loss = initial test plate mass - test plate mass after test completion
[0095] Each group of samples was tested 5 times and the average value was taken. The test results are shown in Table 1.
[0096] Waterproof performance test:
[0097] The test samples of Examples 1-5 and Comparative Examples 1-4 were prepared with reference to the above anticorrosion performance test method, and the initial mass m0 of the test samples was recorded. Then, each test sample was placed in water at room temperature and soaked for 48 hours, then taken out, and the surface water was absorbed with filter paper, and its mass was recorded as m1. The water absorption rate of the coating was calculated according to the mass change. The water absorption rate calculation formula is as follows:
[0098] Water absorption rate = (m1-m0) / m0×100%
[0099] Each group of samples was tested 5 times and the average value was taken. The test results are shown in Table 1.
[0100] Table 1
[0101]
[0102]
[0103] As can be seen from Table 1, by comparing Examples 1-5 and Comparative Examples 1-4, it is found that the antibacterial rates of Examples 1-4 are not much different, and the antibacterial rates against Escherichia coli are all higher than 95%, and the antibacterial rates against Staphylococcus aureus are all higher than 93%. However, the antibacterial rates of Examples 1-4 containing composite modified boron nitride and secondary modified glass flakes are significantly higher than those of Example 5 without secondary modified glass flakes and Comparative Example 1 containing only composite modified boron nitride, Comparative Example 2 containing composite modified boron nitride and glass flakes, Comparative Example 3 containing only secondary modified glass flakes, and Comparative Example 4 containing composite modified boron nitride and secondary modified glass flakes using titanium dioxide to replace titanium dioxide colloid. Among them, the antibacterial activity of Comparative Examples 3-4 is significantly higher than that of Examples 5 and Comparative Examples 1-2, indicating that the addition of secondary modified glass flakes is beneficial to improving the antibacterial performance of the coating, and the synergistic use of composite modified boron nitride and secondary modified glass flakes is beneficial to further improve the antibacterial effect of the coating. The reason may be that during the modification process of the secondary modified glass flakes, titanium dioxide colloid is introduced to form a coordination bond with phytic acid, so that the composite structure of titanium dioxide particles and phytic acid is anchored on the surface of the secondary modified glass flakes, which not only expands the spectral response range of the photocatalytic antibacterial effect of titanium dioxide, but also improves the shortcomings of titanium dioxide when used alone in the matrix resin, and exerts the synergistic effect of titanium dioxide and phytic acid in the antibacterial effect, that is, it has a double-effect bactericidal effect, which helps to inhibit the growth and reproduction of bacteria and increase the antibacterial property of the coating. The present invention uses composite modified boron nitride and secondary modified glass flakes in a coordinated manner. During the coating preparation process, the composite modified boron nitride and secondary modified glass flakes have good dispersibility in the resin matrix, and the two can form a more complete physical and chemical barrier in the coating, effectively preventing the attachment and growth of bacteria.
[0104] By comparing Examples 1-5 and Comparative Examples 1-4, it is found that the salt spray resistance time of Examples 1-4, Comparative Examples 1 and 4 containing composite modified boron nitride and secondary modified glass flakes is significantly higher than that of Example 5 containing only composite modified boron nitride, Comparative Example 2 containing composite modified boron nitride and glass flakes, and Comparative Example 3 containing only secondary modified glass flakes; and the wear mass loss and water absorption rate of Examples 1-4, Comparative Examples 1 and 4 are significantly lower than those of Example 5 and Comparative Examples 2-3, among which Example 1 has the highest salt spray resistance time, the lowest wear mass loss and water absorption rate, indicating that the synergistic use of composite modified boron nitride and secondary modified glass flakes can significantly improve the waterproofness, corrosion resistance and wear resistance of the coating. The reason may be that the present invention increases the dispersibility of the composite modified boron nitride and the secondary modified glass flakes in the resin matrix through modification, and hydrogen bonds, van der Waals forces, electrostatic interactions or covalent bonding may occur between the functional groups on the surfaces of the two, which enhances the interfacial bonding force between the two, and is beneficial to the dispersion and compatibility of the two in the coating. In addition, both boron nitride and glass flakes have layered structures, and the increase in the compatibility of the two helps to form a stable physical barrier and low-friction interface in the coating, preventing water molecules and corrosive media from penetrating into the metal surface and reducing the wear of the coating during friction, which is beneficial to improving the waterproofness, corrosion resistance and wear resistance of the coating. The surface of the composite modified boron nitride uniformly dispersed in the anti-corrosion coating of the present invention is grafted with polyaniline and anti-corrosion ions. Polyaniline, as a conductive polymer with good chemical stability, can participate in the electrochemical reaction of the metal surface, and by accepting the electrons released during the metal dissolution process, a passivation film is formed to inhibit the metal's anodic oxidation process, thereby improving the anti-corrosion performance. At the same time, the secondary modified glass flakes are used in conjunction with composite modified boron nitride. The phytic acid grafted on the surface of the secondary modified glass flakes contains multiple phosphate groups, which can form stable chelates with metal ions. This helps to fix the metal ions in the coating, and can assist the composite modified boron nitride to more effectively disperse and fix the anti-corrosion ions, reducing the risk of them losing their anti-corrosion effect due to dissolution or loss, and improving the uniformity and stability of the anti-corrosion ions in the coating, which is beneficial to the continuous release of anti-corrosion ions during the use of the coating, providing long-term corrosion inhibition effects.
[0105] By comparing Examples 1-4, it is found that the salt spray resistance time of Example 1-3 using polyaniline surface modified boron nitride is higher than that of Example 4 using polydopamine surface modified boron nitride, and the wear mass loss and water absorption rate are significantly lower than those of Example 4. The reason may be that compared with polydopamine, polyaniline is a conductive polymer, and its conductivity enables it to form an electrochemical barrier in the coating, slowing down the corrosion rate, and the nitrogen atoms in polyaniline can form strong chemical bonds with the metal surface, enhancing the adhesion of the coating, which is beneficial to improving the water resistance and wear resistance. At the same time, its chemical activity also helps to form a passivation film, providing additional corrosion protection, while polydopamine itself is not conductive and has relatively low chemical activity, so it is not as effective as polyaniline.
[0106] By comparing Examples 1-3, it was found that the salt spray resistance time of Example 1 in which sodium molybdate was used as the modifier in the preparation process of composite modified boron nitride was significantly higher than that of Examples 2 and 3 in which sodium tungstate and sodium titanate were used as the modifiers, respectively, and the wear mass loss and water absorption rate were significantly lower than those of Examples 2-3. The reason may be that compared with tungstate ions and titanate ions, molybdate ions may have higher chemical activity and stronger chelating ability, and can more effectively form stable chemical bonds with other components in the coating or the metal surface, thereby forming a dense passivation film, thereby providing better protection for the coating.
[0107] By comparing Example 1 and Comparative Example 4, it is found that the antibacterial, waterproof, anti-corrosion and wear resistance of Example 1 are significantly better than those of Comparative Example 4. The reason may be that compared with the introduction of titanium dioxide, the titanium dioxide colloid prepared by the present invention has a higher specific surface area, which may prompt it to form a stronger surface charge, and help the titanium dioxide colloid to more easily react chemically with phytic acid to form a stable coordination bond, thereby increasing the durability of the titanium dioxide colloid in the coating, and during the modification process, the titanium dioxide colloid can form a stable encapsulating adsorption layer on the surface of the glass flakes by chemical bonding and physical adsorption, which increases the surface roughness of the glass flakes, enables it to better combine with the matrix resin, and improves the coating adhesion, wear resistance and anti-permeability, thereby improving the anti-corrosion and waterproof properties.
[0108] In summary, the present invention uses secondary modified glass flakes and composite modified boron nitride in a coordinated manner to improve the antibacterial, anticorrosive, water-resistant and wear-resistant properties of the polysiloxane multifunctional anticorrosive coating, which is beneficial to improving the durability of the coating and increasing the service life of the coating.
Claims
1. A preparation process of a polysiloxane multifunctional anti-corrosion coating, characterized in that: The following steps are involved: Vinyl-terminated methylphenyl polysiloxane, epoxy resin and anhydrous ethanol are put into a stirring tank and mixed and stirred at 500-800rpm and 30-50°C for 20-30min to obtain a mixed slurry A; then the mixed slurry A, composite modified boron nitride, sodium montmorillonite, leveling agent, dispersant and film-forming aid are added to a ball mill and ground to a fineness of ≤30μm to obtain a mixed slurry B; then a curing agent and a defoaming agent are added to the mixed slurry B, mixed and stirred at 80-120MPa and 1000-1500rpm for 30-60min to obtain a polysiloxane multifunctional anti-corrosion coating; the polysiloxane multifunctional anti-corrosion coating is applied and dried to obtain a polysiloxane multifunctional anti-corrosion coating; Alternatively, vinyl-terminated methylphenyl polysiloxane, epoxy resin and anhydrous ethanol are put into a stirring tank and mixed and stirred at 500-800rpm and 30-50°C for 20-30min to obtain a mixed slurry A; then the mixed slurry A, composite modified boron nitride, sodium montmorillonite, filler, leveling agent, dispersant and film-forming aid are added to a ball mill and ground to a fineness of ≤30μm to obtain a mixed slurry B; then a curing agent and a defoaming agent are added to the mixed slurry B, mixed and stirred at 80-120MPa and 1000-1500rpm for 30-60min to obtain a polysiloxane multifunctional anti-corrosion coating; the polysiloxane multifunctional anti-corrosion coating is applied and dried to obtain a polysiloxane multifunctional anti-corrosion coating.
2. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 1, characterized in that: The weight proportion of each raw material component is: 40-60 parts of vinyl-terminated methylphenyl polysiloxane, 5-15 parts of epoxy resin, 1-3 parts of composite modified boron nitride, 10-15 parts of sodium montmorillonite, 1-3 parts of leveling agent, 1-3 parts of curing agent, 1-2 parts of dispersant, 1-2 parts of film-forming aid, 1-2 parts of defoaming agent, 5-12 parts of anhydrous ethanol; Or, 40-60 parts of vinyl-terminated methylphenyl polysiloxane, 5-15 parts of epoxy resin, 1-3 parts of composite modified boron nitride, 10-15 parts of sodium montmorillonite, 4-8 parts of filler, 1-3 parts of leveling agent, 1-3 parts of curing agent, 1-2 parts of dispersant, 1-2 parts of film-forming aid, 1-2 parts of defoaming agent, and 5-12 parts of anhydrous ethanol.
3. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 1 or 2, characterized in that: The epoxy resin is selected from one of epoxy resin E20, epoxy resin E44 and epoxy resin E51.
4. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 1 or 2, characterized in that: The preparation method of the composite modified boron nitride comprises the following steps, measured by weight: S1. Add 0.5-2 parts of hexagonal boron nitride and 0.5-2 parts of aniline to 40-60 parts of phosphoric acid with a concentration of 0.5-2 mol / L, mix and stir evenly, and then ultrasonically treat for 25-40 minutes to obtain a mixed solution A; add 3-4 parts of sodium persulfate to 40-60 parts of phosphoric acid with a concentration of 0.5-2 mol / L, mix and stir evenly, to obtain a mixed solution B; add the mixed solution B to the mixed solution A, and then continuously mix and stir in an ice water bath for 2-4 hours, then filter, wash with ethanol 2-3 times, then wash with water 2-3 times, and then dry to obtain surface-modified boron nitride; S2. The surface modified boron nitride, modifier and water are mixed and stirred evenly in a weight ratio of 1:0.05-0.2:4-6, and then ultrasonically treated for 20-40 minutes, and then vacuum dried at 45-55° C. for 4-6 hours to obtain composite modified boron nitride.
5. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 4, characterized in that: In the step S2, the modifier is selected from one of sodium molybdate, sodium titanate and sodium tungstate.
6. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 4, characterized in that: In parts by weight, step S1 in the method for preparing the composite modified boron nitride may also be: Disperse 1-3 parts of hexagonal boron nitride in 80-100 parts of Tris buffer with a pH value of 8.0-8.5, and then ultrasonically treat for 0.5-2 hours to obtain a dispersion; add 0.5-2 parts of dopamine hydrochloride to the above dispersion, place it in a 55-65°C water bath and mix and stir for 22-25 hours, then filter, wash with ethanol 2-3 times, then wash with water 2-3 times, and then dry to obtain surface modified boron nitride.
7. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 1 or 2, characterized in that: The leveling agent is selected from one of German BYK BYK-323, BYK-345, and BYK-326; the curing agent is selected from at least one of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, anilinomethyltrimethoxysilane, and anilinomethyltriethoxysilane.
8. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 1 or 2, characterized in that: The dispersant is selected from at least one of German BYK-153, BYK-154, and BYK-156; the film-forming aid is selected from at least one of ethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, propylene glycol methyl ether, and propylene glycol butyl ether; and the defoamer is a silicone polyether defoamer.
9. The process for preparing the polysiloxane multifunctional anticorrosive coating according to claim 1 or 2, characterized in that: The filler is a secondary modified glass flake, and the preparation method thereof comprises the following steps, calculated by weight: 4-6 parts of water, 4-6 parts of silane coupling agent KH-560, 25-35 parts of anhydrous ethanol and 8-12 parts of glass flakes are placed at room temperature and 300-600rpm and mixed for 22-25 hours to obtain a mixed solution A; the mixed solution A is centrifuged, the precipitate is collected, washed with water and vacuum dried at 55-65°C to obtain a primary modified glass flake; 1-3 parts of acetic acid and 1-3 parts of water are added to 60-68 parts of anhydrous ethanol, and the pH is adjusted to 3-4 with dilute hydrochloric acid to obtain solution A; 8-12 parts of tetrabutyl titanate are added to 60-68 parts of anhydrous ethanol and mixed and stirred. , obtaining solution B; then adding solution B to solution A at 600-800rpm and 24-26°C and continuously mixing and stirring for 22-25h to obtain titanium dioxide colloid; mixing 1.5-3 parts of primary modified glass flakes, 25-35 parts of anhydrous ethanol, 0.01-0.1 parts of phytic acid and 0.01-0.1 parts of titanium dioxide colloid, placing at 300-500rpm and 75-85°C and mixing and stirring for 3-5h to obtain a mixed solution B; centrifuging the mixed solution B, collecting the precipitate, washing with water and drying in vacuo at 55-65°C to obtain a secondary modified glass flake.
10. A polysiloxane multifunctional anticorrosion coating, characterized in that: Prepared by the process described in any one of claims 1 to 9.
Citation Information
Patent Citations
Water-based polysiloxane resin and preparation method thereof, and finishing coat and preparation method thereof
CN112708077A
Isocyanate cured polysiloxane coating and preparation method thereof
CN117801670A
Preparation method of tannic acid grafted glass flakes and application of tannic acid grafted glass flakes in high-solid anticorrosive coating
CN112226101A
Dual-modified waterborne epoxy resin anticorrosive paint and preparation method thereof
CN113308174A
Water-based metal anticorrosive paint and preparation method thereof
CN114806305A
Cited By
Durable polysiloxane silicone rubber anticorrosive paint and preparation method thereof
CN120795791A